DFT Studies on Isoprene/Ethylene Copolymerization Catalyzed by Cationic Scandium Complexes Bearing Different Ancillary Ligands. Issue 5 (28th April 2017) - Hu, Xiaojie; Kang, Xiaohui; Zhou, Guangli; Wang, Xingbao; Hou, Zhaomin; Luo, Yi
Abstract: The isoprene/ethylene copolymerization catalyzed by cationic rare earth metal complexes [( η 5 ‐C5 Me5 )Sc(CH2 SiMe3 )] + (A ) had afforded alternating isoprene‐ethylene copolymer with rich 3, 4‐polyisoprene microstructures, whereas no isoprene‐ethylene copolymer was observed by using analogous [(PNP Ph )Sc(CH2 SiMe3 )] + (B ) under the same conditions. Theoretical calculations in this work have revealed that, in the case ofA, successive 3, 4‐insertion of isoprene resulted in a noncovalent interaction between the C = C double bond of penultimate unit and the metal center, suppressing the further insertion of monomers due to higher energy barrier and endergonic character. On the other hand, the ethylene pre‐inserted species with alkyl active site is more suitable for the subsequent kinetically and thermodynamically favorable isoprene insertion and copolymerization is therefore realized. In the case ofB, the experimentally observed cis ‐1, 4‐specific homopolymerization of isoprene was the outcome of both kinetic and thermodynamic control. And, the unfavorable ethylene insertion into the isoprene pre‐inserted species with allyl active site could account for the experimental finding that no isoprene‐ethylene copolymer was obtained. These computational results are expected to provide some hints for the design of rare earth copolymerization catalysts. Abstract : DFT studies on isoprene/ethylene copolymerization catalyzed by two cationic scandium speciesA andB (see the Figure) have been carried out. In the case ofA, a backbiting coordination of the C = C double bond of penultimate unit is disadvantageous for the further insertion of monomers into Sc–π‐allyl complexes, which makes the ethylene pre‐inserted intermediate suitable for kinetically favorable isoprene insertion and thus achieves copolymerization. In the case ofB, the thermodynamically unfavorable ethylene insertion into the isoprene pre‐inserted species could account for the experimental finding that no copolymer was obtained.